2017
DOI: 10.1002/slct.201601322
|View full text |Cite
|
Sign up to set email alerts
|

Protonation of Pyridine Monocarboxylate‐N‐Oxides – Determination of Thermodynamic, Absorbance and Ion Interaction Parameters

Abstract: The thermodynamic parameters (pKa, ΔH, ΔG, ΔS) for the protonation of three isomeric pyridine monocarboxylate‐N‐oxides (PCNO) namely picolinate‐N‐oxide (PANO) nicotinate‐N‐oxide (NANO) isonicotinate‐N‐oxide (IANO) were determined in the present study. The pKa determined by potentiometry follow the order: PANO > IANO > NANO at all ionic strengths. The calorimetric results revealed that the PANO protonation was endothermic and the other are exothermic, indicating the entropy driven protonation of PANO while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Thus, these reactions are majorly entropy-driven protonations. The ΔH P for the protonation of formates, acetates, and propionates under similar experimental conditions are 1.28, 1.68, and, 1.08 kJ/mol, respectively; 44 the present study also revealed a similar trend of ΔH P2 for the protonation of the carboxylate group of the ligand. Minofar et al studied the hydration of aliphatic dicarboxylate anions of varying chain lengths and found that the hydrophilic interactions of charged species are dominant over hydrophobic interactions of the alkyl chain up to adipate, and these dianions are encapsulated in hydration shells.…”
Section: Protonation Constantssupporting
confidence: 80%
“…Thus, these reactions are majorly entropy-driven protonations. The ΔH P for the protonation of formates, acetates, and propionates under similar experimental conditions are 1.28, 1.68, and, 1.08 kJ/mol, respectively; 44 the present study also revealed a similar trend of ΔH P2 for the protonation of the carboxylate group of the ligand. Minofar et al studied the hydration of aliphatic dicarboxylate anions of varying chain lengths and found that the hydrophilic interactions of charged species are dominant over hydrophobic interactions of the alkyl chain up to adipate, and these dianions are encapsulated in hydration shells.…”
Section: Protonation Constantssupporting
confidence: 80%
“…Upon complexations, extractants with dissociable protons are prone to protonation and deprotonation, and thus, a change in the hydrogen ion concentration (pH) is a good indicator of complexation progress. In the present study, the sequential progress of complexation is probed by adding a concentrated ligand solution into a fixed concentration of a metal solution and monitoring the pH after each addition of the ligand. Potentiometric data were analyzed by Hyperquad program , to deduce the species present along with stability for complex formation during the course of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical nature of the participating ligand and the geometry arrived by its coordination on the equatorial plane has phenomenal effects on the intensities and positions of electronic transitions of the uranyl ion in the range of 380–480 nm arising from vibronic perturbed electronic transitions. , The protonation process is an inseparable mechanism while studying the complexation phenomenon, especially with the protonated/deprotonated ligands; and the protonation thermodynamic data are a prerequisite to obtain the complexation thermodynamics data. The present studies utilized the protonation data from our previous work .…”
Section: Resultsmentioning
confidence: 99%